2008
DOI: 10.1021/nl801394w
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Anisotropic Wetting on One-Dimensional Nanopatterned Surfaces

Abstract: This communication reports strongly anisotropic wetting behavior on one-dimensional nanopatterned surfaces. Contact angles, degree of anisotropy, and droplet distortion are measured on micro- and nanopatterned surfaces fabricated with interference lithography. Both the degree of anisotropy and the droplet distortion are extremely high as compared with previous reports because of the well-defined nanostructural morphology. The surface is manipulated to tune with the wetting from hydrophobic to hydrophilic while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
175
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(180 citation statements)
references
References 31 publications
5
175
0
Order By: Relevance
“…Anisotropic wetting may be useful for easy-clean coatings. 22 In summary, we have demonstrated that manipulation of surface properties can be done by the surface texturing of the thin urushiol film and the subsequent polymer brush growth. The surface showed superhydrophilicity because PMTAC polymer brushes were grown on the textured surface.…”
Section: ¹1mentioning
confidence: 86%
“…Anisotropic wetting may be useful for easy-clean coatings. 22 In summary, we have demonstrated that manipulation of surface properties can be done by the surface texturing of the thin urushiol film and the subsequent polymer brush growth. The surface showed superhydrophilicity because PMTAC polymer brushes were grown on the textured surface.…”
Section: ¹1mentioning
confidence: 86%
“…directional) surface structures (e.g. grooves, pillars and nanowires) [7][8][9][10][11] or surface chemistry (e.g. hydrophilic/hydrophobic patterns).…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropic wettability has attracted more attentions of the research community. [1][2][3][4][5][6][7][8][9][10][11][12][13] Inspired by the natural microstructure like rice leaf, artificial anisotropic wetting surfaces have been studied recently. Dual-scale micro-nano structures have been prepared by different techniques and their wettability have been studied.…”
Section: Introductionmentioning
confidence: 99%